A note on transitive permutation groups of degree twice a prime - Potočnik, Primož (Ars mathematica contemporanea, 2008)
In this note, we consider transitive permutation groups of degree ?$2p$?, where ?$p$? is an odd prime, that admit blocks of imprimitivity of size 2 but no blocks of imprimitivity of size ?$p$?.
Keywords: matematika; permutacijske grupe; teorija grup